Gastrodiplomacy: Assessing the role of food in decision-making - Spence, C (BioMed Central, 2016)
This review addresses a number of questions around the relation between food and decision-making/social behaviour, including the following: Can food be used as a tool of political persuasion? What role, if any, does the food we eat have over the decisions we reach? Do we bond with those with whom we happen to share a meal? And is it ever ethical to accept a free lunch? Can the provision of food be used to enhance creativity/productivity? Ultimately, the case is made that what we eat plays a far more important role in cognition, decision-making, and impression formation than most people realize.